Integration of the use of “Nasi Tumpeng” in the teaching of BIPA as one of Indonesian local cultural wisdom - Raden Yusuf Sidiq Budiawan (Universitas Indraprasta PGRI, 2017)
This study aimed to describe the potential of teaching BIPA integrated with rice cone as a philosophical and cultural wisdom Indonesia. Integrating learning with cultural language is intended to provide an understanding of culture that refers to the ability to choose the form of the language according to the sociocultural context in communication Indonesian. This qualitative descriptive study begins with the collection of data with the literature search techniques and in-depth interviews. Data analysis stage starts with observation data to identify the values of local wisdom in rice cone and the potential for BIPA learning that can be integrated with one of the traditional Indonesian cuisine. Presentation of the results of the data analysis described formally and informally. This study shows that rice cone store various life values of form and composition, such as a character close to nature, surrender to God, tolerance, respect, love art, prudence, togetherness, harmony helpful to others, religious, self-controlled , surrender, simple, stoic, strong, and resilient. Rice cone can also be integrated in a cultural learning, speaking, listening, writing, reading, and vocabulary with a variety of activities, such as cooking demonstrations, mini-paper, or a game with the flash cards, cue cards, jumbled paragraphs, jumbled sentences, jumbled words, etc.